Safety and efficacy of ensifentrine in COPD: A systemic review and meta-analysis - Ambanna Yappalparvi (21260018) (2024)
Background Chronic obstructive pulmonary disease (COPD) significantly impacts global health due to persistent airflow limitation and inflammation. Despite standard therapies, symptoms persist. Ensifentrine, targeting both bronchoconstriction and inflammation as a dual phosphodiesterase 3 and 4 inhibitor, offers a promising therapeutic advancement for COPD management. This meta-analysis evaluates the safety and efficacy of ensifentrine in improving lung function, dyspnea, and quality of life in COPD patients. Methods We searched PubMed, Embase, and Web of Science through August 2024 for randomized controlled trials evaluating ensifentrine in COPD patients over a minimum of four weeks. Data extraction and screening utilized Knowledge software, and meta-analyses were performed using R v4.4 with a random-effects model. Results From 206 studies identified, four met our inclusion criteria. Ensifentrine improved FEV1 significantly at a dose of 3 mg (LS mean difference: 40.90 mL; 95 % CI: 19.65–62.15). It also improved dyspnea as measured by the Transition Dyspnea Index (TDI) (LS mean difference: 0.91; 95 % CI: 0.61–1.21) and quality of life according to the St. George's Respiratory Questionnaire-C (SGRQ-C) scores (LS mean difference: −1.92; 95 % CI: −3.28 to −0.55). Safety profiles were comparable between the ensifentrine and placebo groups, with no significant increase in treatment-emergent adverse events (TEAEs) (RR: 1.02; 95 % CI: 0.94–1.10). Conclusion Ensifentrine significantly enhances lung function, reduces dyspnea, and improves quality of life in COPD patients, especially at a 3mg dose. These benefits, coupled with a stable safety profile, support its use as an adjunctive therapy in COPD management. Other Information Published in: Respiratory Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rmed.2024.107863